Live birth prevalence of major congenital anomalies in the United Arab Emirates - Hiba Adam; Nadirah Ghenimi; Hassib Narchi; Amir Ahmad; Omniyat M. Al Hajeri; Iffat Elbarazi; Rami H. Al-Rifai; Luai A. Ahmed (Scientific Reports)
Abstract Major congenital anomalies (MCAs) significantly contribute to perinatal mortality and morbidity. Globally, the United Arab Emirates has the sixth-highest prevalence rate of congenital anomalies. The lack of clear baseline prevalence data for MCAs impedes the development of interventions to alleviate this burden. This study aimed to estimate the live birth prevalence of perinatally diagnosed MCAs in a sample of the Emirati population. The analysis was based on a cohort of all singleton live births in the Mutaba’ah study. Minor anomalies were excluded and the live birth prevalence of MCAs was estimated as the number of affected births per 1000 live births. Among 4034 singleton live births, 284 neonates were diagnosed with at least one MCAs, corresponding to a live birth prevalence of 70.4/1000 live births (95% confidence interval: 62.7–78.7). Of the 284 neonates, 86% presented with single-system anomalies, while 14% displayed multi-system involvement. The circulatory system was predominately affected (21.3/1000), followed by the urinary, genital, and musculoskeletal systems. Within the circulatory system, anomalies of cardiac septa (88.6%) and great arteries (70.2%) were the most prevalent. The findings indicate a relatively high live birth prevalence of MCAs. Further studies are needed to identify risk factors and explore screening and prevention strategies.